MULTIMODAL IMAGING OF TWO UNCONVENTIONAL CASES OF BARTONELLA NEURORETINITIS. Issue Volume 16:Issues 1(2022) (January 2022) - Michel, Zachary; Redd, Travis; Bhavsar, Kavita V.
Abstract : Purpose: To report two cases of cat-scratch fever with atypical posterior segment manifestations. Methods: Two cases were retrospectively reviewed. Results: A 27-year-old woman presented with painless blurring of central vision in her left eye. Clinical examination revealed a small focal area of retinitis within the macula associated with a subtle macular star. Spectral-domain optical coherence tomography showed a hyper-reflective inner retinal lesion in addition to subretinal and intraretinal fluid as well as hyperreflective foci within the outer plexiform layer. Serology was positive for anti– B. henselae IgM (titer 1:32). A 34-year-old woman presented with painless loss of vision in both eyes associated with headaches and pain with extraocular movement. Spectral-domain optical coherence tomography depicted subretinal fluid, intraretinal fluid, and hyperreflective deposits within the outer plexiform layer. A focal collection of vitreous cell was observed overlying the optic nerve in the left eye. Bilateral disk leakage was identified on fluorescein angiography. Serology revealed high-titer anti– B. henselae antibodies (IgM titers 1:32, IgG titers 1:256). Conclusion: Our cases highlight the necessity of recognizing more unusual posterior segment presentations of ocular bartonellosis. Multimodal retinal imaging including spectral-domain optical coherence tomography may help better characterize lesions. Abstract : We report multimodal retinal imaging in two cases of cat-scratch disease with atypical posterior segment manifestations including one case of focal retinitis and another case presenting with bilateral optic nerve edema.